Hubungan Antara Keaktifan Berorganisasi Pustat Informasi Konseling Remaja (PIK-R) Dengan Hasil Belajar Siswa Sekolah Menengah Atas Negeri 3 Padang Panjang - Azan Jumat Mulia; Setiawati Setiawati (Universitas Negeri Padang, 2022)
The research was motivated by the low learning outcomes of students who were suspected of having a relationship with participating in the PIK-R organization at State High School 3 Padang Panjang. The objectives of this study are as follows: (1) To describe the activity of students in the PIK-R organization at the State Senior High School 3 Padang Panjang. (2) To see an overview of the learning outcomes obtained by the students of the State Senior High School 3 Padang Panjang. (3) To find out the relationship between the activeness of the PIK-R organization and its learning outcomes at State Senior High School 3 Padang Panjang.This type of research is quantitative with a correlational approach. The aim is to examine the correlation between PIK-R's organizational activity and learning outcomes. The population of this study was 36 people, the sampling technique was Stratifide Random Sampling and taken as many as 70%, namely as many as 26 people. The data collection technique used is a questionnaire and using the Rank Order formula.The results and discussion of this study are as follows: (1) The description of the organizational activity of PIK-R students at the State High School 3 Padang Panjang is categorized as low. (2) The description of student learning outcomes of State Senior High School 3 Padang Panjang is categorized as medium. (3) There is a significant correlation between PIK-R's organizational activity and student learning outcomes of State Senior High School 3 Padang Panjang. It is hoped that it can increase activeness in organization for State Senior High School 3 Padang Panjang